Tegumentary and visceral leishmaniases in Brazil: emerging anthropozoonosis and possibilities for their control - Marzochi Mauro Célio de A.; Marzochi Keyla Belízia F. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
The existence of a number of different species of Leishmania, the persistent increase in the infection rate of diseases caused by this parasite (tegumentary and visceral forms), the different epidemiological situations found in regions of both recent and older colonization, and the trend towards urbanization have led to the adoption of different strategies to control leishmaniases in Brazil. The control measures involve studies related to the parasite, vectors, sources of infection (animal and human), clinical aspects, geographical distribution, historical and socioeconomic factors, integration of health services, and adequate technologies for diagnosis, treatment, and immunoprophylaxis. Finally, successful control requires work with human communities, involving education, provision of information, health promotion, and participation of these communities in the planning, development, and maintenance of control programs.